2001
DOI: 10.1038/sj.ejcn.1601164
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reproducibility of a self-administered questionnaire to determine dietary supplement users among Japanese

Abstract: Objective: To evaluate reproducibility and validity of a self-administered food frequency questionnaire (FFQ) to determine the dietary supplement use. Design: Questionnaire data were compared with dietary records (DR) in four 7 day periods for validity. FFQ1 and FFQ2 administered at an interval of approximately one year were compared for reproducibility. Setting and subjects: A total of 361 samples were selected for a validation study of a questionnaire from the subgroup of the Japan Public Health Center-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 15 publications
3
22
3
Order By: Relevance
“…This was true also for Dorant et al, who reported a PPV of 96.4% and a NPV of 82.7% (Dorant et al, 1994). In contrast to our data, Ishihara et al showed a higher NPV (97.2%) than PPV (64.3%) (Ishihara et al, 2001).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This was true also for Dorant et al, who reported a PPV of 96.4% and a NPV of 82.7% (Dorant et al, 1994). In contrast to our data, Ishihara et al showed a higher NPV (97.2%) than PPV (64.3%) (Ishihara et al, 2001).…”
Section: Discussioncontrasting
confidence: 55%
“…Two previous studies, one in the Netherlands and one in Japan, have reported a slightly lower overall sensitivity (65.9 and 75.0%, respectively) with a prevalence of 25.7% dietary supplement users among participants in the study from the Netherlands and 10% a year-round dietary supplement use in the Japanese study (Dorant et al, 1994;Ishihara et al, 2001). The overall specificity in these two studies was 98.5 and 95.4%, respectively.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, the lack of awareness of children's supplements may be one reason for the low prevalence of children's supplement use in this survey. The supplement use by adults in the United States has been increasing (19,(29)(30)(31) and similar trends, although somewhat delayed, have been observed in Japan (7)(8)(9). The parents who were aware of the existence of children's supplements generally displayed an affirmative approach to children's supplement use.…”
Section: Discussionmentioning
confidence: 80%
“…The number of adult supplement users in Japan has recently become larger and larger, as in the United States and other developed countries (7)(8)(9)(10). According to recent studies in various areas of Japan, 55% of men and 61% of women have used supplements ( 10 ).…”
mentioning
confidence: 99%
“…Assessment of supplement use by the food frequency questionnaire is also reliable. 18,19 Participants typically returned food frequency questionnaires every 4 years during the follow-up period (1984( , 1986( , 1994( , and 19981991 and1995 in NHS II;1986, 1994, and 1998 in HPFS), and vitamin D intake was reset for each participant at each of these time points according to the most recent level of intake.…”
Section: Assessment Of Vitamin D Intakementioning
confidence: 99%